Timor-Leste : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Timor-Leste. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2021)
Although Timor-Leste has made considerable progress in many areas since its independence in 2002, it faces significant medium-term challenges. The nation has pressing development needs, young institutions, and is highly dependent on oil. Oil revenues from active fields, which have been the main source of funding for government spending, are drying up. The non-oil private sector economy remains underdeveloped and lack of good jobs and high youth unemployment are serious concerns.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements; International Organizations; Monetary Policy; Observance; Timor-Leste, Democratic Republic of